A student led computational screening of peptide inhibitors against main protease of SARS‐CoV‐2. Issue 1 (9th October 2021) - Khan, Anika Tajrian; Chowdhury, Golam Mahmud; Hafsah, Juwairiyah; Maruf, Md; Raihan, Md Riyad Hossen; Chowdhury, Md Talha; Nawal, Nafisa; Tasnim, Nishat; Saha, Pranto; Roy, Prottoy; Tabassum, Raya; Rodrigues, Souvick Patrick; et al.
Abstract: The main protease of SARS‐CoV‐2 is a promising drug target due to its functional role as a catalytic dyad in mediating proteolysis during the viral life cycle. In this study, experimentally proven 14 HIV protease peptides were screened against the main protease of SARS‐CoV‐2. Fourteen middle and high school "student researchers" were trained on relevant computational tools, provided with necessary biological and chemical background and scientific article writing. They performed the primary screening via molecular docking and the best performing complexes were subjected to molecular dynamics simulations. Molecular docking revealed that HIP82 and HIP1079 can bind with the catalytic residues, however after molecular dynamics simulation only HIP1079 retained its interaction with the catalytic sites. The student researchers were also trained to write scientific article and were involved with drafting of the manuscript. This project provided the student researchers an insight into multi‐disciplinary research in biology and chemistry, inspired them about practical approaches of computational chemistry in solving a real‐world problem like a global pandemic. This project also serves as an example to introduce scientific inquiry, research methodology, critical thinking, scientific writing, and communication for high school students. Abstract : Interactions between antiviral peptide and main protease of SARS‐CoV‐2 are obtained by molecular docking and dynamics